Shaping the future: Satryo Brodjonegoro’s blueprint for education in Indonesia - Abdullah Helmy; Brian Fairman; S. Suparto; Adam Voak; Hurriyet Babacan (Research and Development in Education (RaDEn), 2025)
The election of the new Indonesian Government heralds a new direction in higher education in Indonesia. Higher education is critical to Indonesia amidst significant global and national challenges, including globalisation, the uptake of advancing technologies, and climate change. This paper examines the potential role and leadership of Satryo Soemantri Brodjonegoro, the newly appointed Indonesian Minister for Higher Education, Science and Technology, can play in strengthening Indonesia’s resilience. As a prominent figure in academia and the education bureaucracy, Brodjonegoro’s work has significantly influenced the direction of Indonesia’s human capital development landscape. This review synthesises his academic publications, policy initiatives and strategic vision, which reveals a focus on driving innovation, enhancing research capacity, and promoting interdisciplinary collaboration within Indonesia's further education system. Central to Brodjonegoro’s thinking is that human capital is a catalyst for national development, and he is focused on preparing Indonesia for the demands of the Fourth Industrial Revolution. This paper also contextualises his work within global trends in Higher Education reform, exploring how his leadership aligns with international best practices and contributes to the broader discourse on education and technological advancement in developing economies. By critically analysing Brodjonegoro’s body of work and its practical implications, this review attempts to provide insights into his potential long-term impact on Indonesia's educational reform and it’s positioning as a knowledge-driven economy.